PENERAPAN SISTEM ELEKTRO PNEUMATIK PADA ALAT STEMPEL OTOMATIS MASA KADALUARSA MAKANAN DAN MINUMAN BERBASIS PROGRAMMABLE LOGIC CONTROLLER (PLC) - T, Satriana; Damayanti, Eva (Jurnal TEDC; Vol 18 No 3 (2024): JURNAL TEDC, 2024)
The development of industrial technology has enhanced efficiency and productivity in production. The implementation of an electro-pneumatic system in an automatic stamping tool based on Programmable Logic Controller (PLC) combines fast and powerful pneumatic motion with precise electrical control, enabling automation and reducing human intervention. This research aims to determine the optimal air pressure and piston force, and to evaluate factors affecting the quality of automatic stamping, such as media, stamp shape, and stamping time. The results show that an air pressure of 3 bar produces the best stamp, with cardboard, plastic, and wood being the most effective media. The rectangular stamp shape provides the best results, while the triangular shape performs the worst. A contact duration of 2 to 3 seconds is the most effective, whereas durations longer than 5 seconds reduce the quality of the stamp. The piston force reaches 60.288 N on the forward stroke and 60.203 N on the return stroke, indicating good stability. This technology enables efficient automated production, minimizes errors, and increases productivity.